2001
DOI: 10.1007/s002770100304
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with all-trans retinoic acid in acute promyelocytic leukemia reduces early deaths in children

Abstract: All-trans retinoic acid (ATRA) is a known inducer of differentiation in acute promyelocytic leukemia. To improve the outcome of children with acute promyelocytic leukemia, ATRA has been applied since 1994 as an additional induction element inthe AML-BFM 93 study. In a retrospective study, we compared 22 children treated with ATRA (median age: 9.3 years; range: 1.8-16.3) with 22 patients receiving conventional therapy (median age: 12.3 years; range: 3.2-16.7). Twenty-one of the children achieved complete remiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
73
2
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 15 publications
(12 reference statements)
4
73
2
3
Order By: Relevance
“…Treatment with As 2 O 3 achieves remission rates of more than 90%, which is similar to data from children treated with ATRA and chemotherapy. 2,3 There is however no data regarding the use of As 2 O 3 as primary therapy in children. Ma Jun et al in their study of 62 children with relapsed APML showed remission rates of 81% with a 7-year DFS of 65% (Blood 2001; abstract 3119).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with As 2 O 3 achieves remission rates of more than 90%, which is similar to data from children treated with ATRA and chemotherapy. 2,3 There is however no data regarding the use of As 2 O 3 as primary therapy in children. Ma Jun et al in their study of 62 children with relapsed APML showed remission rates of 81% with a 7-year DFS of 65% (Blood 2001; abstract 3119).…”
Section: Discussionmentioning
confidence: 99%
“…1 The frontline therapy for APML using a combination of ATRA and chemotherapy has shown initial remission rates of 69-97% with event-free survival (EFS) ranging between 64 and 77% in studies from various countries including India. [2][3][4][5][6] Treatment with ATRA, however, is not financially possible for all patients in economically poor countries and hence alternative therapeutic strategies have been explored. Arsenic trioxide (As 2 O 3 ) was initially used in the treatment of relapsed APML with remission rates of 80-90% and long-term DFS of 60-80%.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with acute promyelocytic leukemia, the early death rate due to coagulopathy has dropped significantly with the introduction of all-trans-retinoic acid. 27 The death in CR rate in AML increased to an unacceptably high level (15.3%) in study AML-92/94. This contributed to the slightly inferior overall survival when study AML-92/94 was compared with AML-87.…”
Section: Discussionmentioning
confidence: 99%
“…The HL-60 cell line was established from peripheral blood leukocytes of a patient originally diagnosed with acute promyelocytic leukemia (4), which was retrospectively re-evaluated to be acute myeloblastic leukemia (7). HL-60 cells undergo G 0 cell cycle arrest and myeloid differentiation in response to RA or monocytic differentiation in response to 1,25-dihydroxyvitamin D 3 . Induced differentiation depends on hyperactive MAPK signaling (1,8).…”
mentioning
confidence: 99%